Analisis Faktor Harga, Mutu Produk, dan Respons Layanan Terhadap Kepuasan Pelanggan Percetakan Digital Zeto Pixel Creative - Fadilanata Efendi; Hendri Herman; Lukman Hakim (Asosiasi Ide Bahasa Kepri, 2026)
This research seeks to examine and explain how pricing, product quality, and service responsiveness influence customer satisfaction in a digital printing business. A quantitative method with an associative design was applied to identify the relationships among variables. The study involved all customers of Zeto Pixel Creative Printing, totaling 71 respondents, selected through a saturated sampling technique. Data were collected using a structured questionnaire that had passed validity and reliability assessments. Furthermore, the data were processed using multiple linear regression analysis, including simultaneous testing through the F-test and partial testing through the t-test. The findings reveal that price, product quality, and service speed collectively have a statistically significant impact on customer satisfaction. This is demonstrated by the calculated F-value exceeding the critical value and a significance level below the accepted threshold. Individually, each independent variable also shows a meaningful effect, as indicated by their respective t-values, which are higher than the standard reference value. These results suggest that better pricing strategies, improved product standards, and faster service delivery contribute positively to enhancing customer satisfaction. Therefore, business managers are encouraged to optimize pricing policies, maintain product excellence, and ensure efficient service to strengthen customer satisfaction.